Insufficiency Fracture of the Superior and Inferior Pubic Rami in a Patient with Osteomalacia: Case Report - Barış Nacır; Burcu Duyur Çakıt; Bünyamin Koç; Meryem Saraçoğlu; Hatice Rana Erdem (Galenos Yayinevi, 2010)
Insufficiency fractures are subtype of stres fractures which occur when normal or physiological stresses are placed on weakened bone. These fractures occur in a variety of conditions in which the mineral content or the elasticity of bone is abnormal. The most common cause of insufficieny fracture is postmenopausal osteoporosis. The other important causes are senile osteoporosis, pelvic irradiation, corticosteroid treatment and rheumatoid arthritis. They also occured in vitamin D deficieny/osteomalacia. The diagnosis of pelvic insufficiency fracture due to osteomalacia should be suspected in a postmenopausal women presenting with severe groin and buttock pain and weakness.We presented here the clinical and radiological findings of superior and inferior pubic ramus insufficiency fracture in a patient with osteomalacia. (Osteoporoz Dünyasından 2010;16:44-8)